Strengthening Community Involvement: An In-Depth Exploration of the Community-Based Tourism (CBT) Approach in Lamajang Tourism Village, Bandung Regency - Andjanie, Isabella Fitria; Asyifa, Nurul; Pratama, Ricky Karya; Furqan, Alhilal (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
One of the challenges in realizing community-based tourism villages is the lack of experience among local communities in tourism activities’ development and management. Therefore, a comprehensive approach based on Community-Based Tourism (CBT) is needed. Lamajang Tourism Village, known for its cultural tourism potential, is developing its natural tourism. This research aims to assess and evaluate the readiness of community participation to manage tourism potential to become a quality, attractive, and sustainable tourism product. The research method used in this study is a descriptive qualitative approach. Data collection techniques consist of spatial and field observations, interviews with various tourism stakeholders and local community figures, and analysis of policy documents of the Bandung Regency government. The assessment framework and indicators are in the Handbook on Community-Based Tourism: How to Develop and Sustain CBT. This research generates several conclusions and recommendations, including the need for evaluation and optimization in particular stages of the CBT approach to advance Lamajang village, which is still considered an initial phase of tourism village, towards a developing/independent tourism village.